Libation - a unifying factor between the performing and the visual arts - Ofori, Henry Asiam (2012)
A thesis submitted to the Board of Postgraduate Studies, Kwame Nkrumah University of Science and Technology, Kumasi, in partial fulfilment of the requirements for the award of the Degree of Master of Arts in African Art,